Entomopathogens of Anαcridium αegyptium L. in Crete - Roditakis Ν. Ε.; Kollaros, D.; Legakis Α. (ENTOMOLOGIA HELLENICA, 2002)
The entomopathogenic fungus Beauveria bassiana (Bals.) Vuil. was recorded for the first time on Anacridium aegyptium L. in Crete. The insects were fed on pieces of leaf subjected to a serial dilution of spores over three to four orders of magnitute. Comparative studies on the virulence of B. bassiana (I 91612 local isolate) and Metarhizium anisopliae var. acridum (IMI 330189 standard isolate of IIBC) showed that M. anisopliae var. acridum was more virulent than B. bassiana at a conidial concentration lower or equal to 106 per ml while they were similarly virulent on first stage nymphs at 107 conidia per ml.